Researches of health and level of physical development for students. - Turchina N.I; Korobeynikov G.V; Popadyukha J.A (Kharkov National Pedagogical University, 2010)
The level of physical development and peculiarities of health in student were studied. 50 students of humanitarian specialties with two groups for health states: general and special medical was diagnostics. The study are showed that states of cardio-vascular system and physical performance are changes of structure of health in students of special groups. This data are indicate on improve of cardio-vascular system of students with differ level of health as need of attention of physical education as general factors of physical performance formed.